Prestige of the medical profession. Is there a connection between feminization and decreased prestige? - Bogusz, Bogusz (Polish Journal of Public Health, 2018)
Introduction. Since the dawn of time, one of the characteristics of the medical profession has been its high prestige. It should be underlined, however, that up until the middle of the 19th century doctors were almost exclusively men. For women, who on the wave of emancipation movements, sought to obtain formal opportunities for becoming a physician, studying medicine and obtaining medical practices were rendered impossible and ultimately hindered due to sex discrimination. Since the beginning of the 20th century, the medical profession has begun to succumb to feminization and women’s domination has remained till this day. Aim. The aim of this article is to present results of research analyzing the position of female doctors in the hierarchy of professional prestige. Material and methods. Results presented in the article are an outcome of qualitative and quantitative questionnaire studies. Quantitative studies were conducted in 2018 on a representative group of 600 adult Poles. In qualitative research, 29 direct interviews with female doctors were conducted. The research sample was selected using snowball sampling. The respondents were physicians with different seniority who were in the process of specialization or with the title of specialist in the field of eighteen medical specialties. Results. Among twenty of the evaluated professions, the highest positions in the hierarchy of prestige was obtained by physicians, firefighters and university professors. In direct interviews, female doctors confirmed that their profession enjoys societies’ respect; however, the level of respect for numerous reasons has decreased compared to the past. Some of the respondents attributed this fall to feminization of medicine. Conclusions. A discrepancy was observed between the physicians’ and society’s opinions. In physicians’ opinion, for various reasons (also due to feminization), the prestige of the medical profession has significantly decreased compared to the past.